Optimalisasi Filter Sumur Bor dan Embung ITK Berbasis Tenaga Surya untuk Peningkatan Pelayanan Sarana dan Prasarana - Priyanto, Yun Tonce Kusuma; Farid, Mifta Nur; Dewanto, Muhammad Ridho; Sugiarto, Kharis; saputra, Riza Hadi (Politeknik Harapan Bersama Tegal, 2025)
The limited supply of conventional energy poses a challenge in operating essential facilities at Institut Teknologi Kalimantan (ITK), particularly in the water filtration system and reservoir management. To address this issue, this study proposes the implementation of an off-grid Solar Power Plant as a solution to enhance energy independence and improve the quality of clean water services on campus. This research aims to design and analyze the performance of an off-grid Solar Power Plant system in supporting water pump operations while evaluating its efficiency in providing sustainable energy. The designed system utilizes three solar panels with a total capacity of 1,635 WP, which is sufficient to meet the 243 W AC pump power demand. The generated energy is regulated using a Maximum Power Point Tracker (MPPT) to optimize power conversion and minimize energy losses. Additionally, a 1,000 Watt Pure Sine Wave inverter is employed to ensure the pump operates stably, while excess energy is stored in a 24V 180 Ah battery to maintain system operation during cloudy conditions or nighttime. The calculations indicate an energy surplus of 5.33 kWh, reinforcing the system’s reliability in meeting the energy needs of the water pump. With a recorded pump efficiency of 55.5%, this study demonstrates that the designed PLTS system is effective in providing sustainable energy. The implementation of an off-grid Solar Power Plant has proven capable of supporting optimal water pump operations, enhancing campus energy independence, and reducing reliance on conventional electricity sources.